2005
DOI: 10.2460/ajvr.2005.66.938
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and preliminary characterization of a novel Helicobacter species from swine

Abstract: Findings of this study indicate that development of gastric mucosal ulcers and ulceration of the nonglandular pars esophagea in pigs may be associated with gastric colonization by swine-origin Helicobacter spp, which are similar to H pylori isolated from humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…and once or twice curved Helicobacter pylori-like bacteria) can colonize the stomach of pigs [5,7,13]. Findings from this study of the prevalence of Helicobacter spp.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…and once or twice curved Helicobacter pylori-like bacteria) can colonize the stomach of pigs [5,7,13]. Findings from this study of the prevalence of Helicobacter spp.…”
Section: Discussionmentioning
confidence: 95%
“…Gastritis is the result of a natural infection with H. pylori in humans [26] and conventional pigs [13] or an experimental induced infection in gnotobiotic piglets [3,14,15], miniature pigs [12] and conventional piglets [22]. In both, humans and pigs, the presence of H. pylori correlates with an inflammatory response, but there are differences in inflammatory cell population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have described this pathogenesis in gastric ulcers lesions (Embaye et al 1990, Krakowka et al 1995, Argenzio & Eisemann 1996, Friendship 2006). In addition, Krakowka et al (2005) suggested that the porcine gastric ulcer disease complex may involve gastric colonization with Helicobacter pylori-like bacteria, but additional studies would help to clarify the association of the bacteria with the gastric ulcers development.…”
Section: Introductionmentioning
confidence: 99%
“…PCV2 is the essential infectious component of postweaning multisystemic wasting syndrome (PMWS) , Meehan et al 2001, Krakowka et al 2005, which is an economically important disease of piglets characterized by wasting and multisystemic lesions, including granulomatous lymphadenitis with lymphoid depletion, hepatitis, pneumonia, and myocarditis , Chae 2004). The demonstration of high or moderate amounts of PCV2 antigen or nucleic acids in close association with characteristic microscopic lesions confirms the diagnosis of PMWS (Sorden 2000).…”
Section: Introductionmentioning
confidence: 99%